KORELASI PROGRAM PEMBINAAN KEAGAMAAN TERHADAP KECERDASAN SPIRITUAL SISWA - Khairun Nisa (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2009)
The objective of the national education that has not been substantially achieved is to promote a generation who believe in One God and have a good character. Educational institutions which are designed to achieve this do only support students’ intellectual education instead of students’ spiritual well-being. Therefore, compre-hensive evaluation on the application of education through Religious Supervisory Program as a technical way should be implemented to achieve the objective of the national education. This paper analyses, the way to enhance spiritual well-being of students.